2016
DOI: 10.1126/science.aad1893
|View full text |Cite|
|
Sign up to set email alerts
|

Large-scale magnetic fields at high Reynolds numbers in magnetohydrodynamic simulations

Abstract: The 11-year solar magnetic cycle shows a high degree of coherence in spite of the turbulent nature of the solar convection zone. It has been found in recent high-resolution magnetohydrodynamics simulations that the maintenance of a large-scale coherent magnetic field is difficult with small viscosity and magnetic diffusivity (≲10 (12) square centimenters per second). We reproduced previous findings that indicate a reduction of the energy in the large-scale magnetic field for lower diffusivities and demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
125
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 25 publications
11
125
2
Order By: Relevance
“…Our results appear to stand apart from similar studies in full spherical shells (e.g., Nelson et al 2013;Hotta et al 2016) in that the differential rotation is strongly quenched as a function of the magnetic Reynolds number. However, in Nelson et al (2013) the values of Rm (=2πRe M ) correspond to a range of 8 .…”
Section: Differential Rotation and Meridional Circulationcontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results appear to stand apart from similar studies in full spherical shells (e.g., Nelson et al 2013;Hotta et al 2016) in that the differential rotation is strongly quenched as a function of the magnetic Reynolds number. However, in Nelson et al (2013) the values of Rm (=2πRe M ) correspond to a range of 8 .…”
Section: Differential Rotation and Meridional Circulationcontrasting
confidence: 99%
“…This is roughly consistent with our results. On the other hand, Hotta et al (2016) reached higher values of Re M than in the present study, but no strong quenching was reported. The reason might be that their models are rotating substantially slower than ours, leading to weaker magnetic fields and a weaker back-reaction to the flow.…”
Section: Differential Rotation and Meridional Circulationcontrasting
confidence: 89%
See 2 more Smart Citations
“…Thus the natural way of studying the solar dynamo is by solving the basic magnetohydrodynamic (MHD) equations in a rotating spherical shell, encompassing the SCZ. However, though substantial progress has been made in recent years in studying fundamental dynamo mechanisms (e.g., Charbonneau 2014; Augustson et al 2015;Featherstone & Miesch 2015;Hotta et al 2016;Käpylä et al 2016;, MHD simulations still cannot capture all processes relevant to the solar dynamo and the solar cycle (Fan & Fang 2014;Karak et al 2015). One reason could be that these simulations do not produce sufficient flux emergence in the form of tilted bipolar magnetic regions (BMRs) that we see in the solar observations (e.g., Wang & Sheeley 1989).…”
Section: Introductionmentioning
confidence: 93%